2021
DOI: 10.1097/brs.0000000000004278
|View full text |Cite
|
Sign up to set email alerts
|

Disc and Vertebral Body Morphology From Birth to Adulthood

Abstract: Objective. The aim of this study was to describe the morphology of intervertebral discs and vertebral bodies during growth in asymptomatic children and adolescents. Summary of Background Data. Earlier studies demonstrated that spinal growth occurs predominantly in vertebral bodies. This axiom introduced a vertebral-body-focus for unravelling etiological questions and achieve growth-modulation in young spinal deformity patients. Recent studies show the importance of the intervertebral discs in the early phases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Nevertheless, mechanical instabilities due to rotational effects could be more relevant than lateral buckling, since intervertebral rotations at end vertebrae and higher torsion moments have been previously described [28,29]. Vertebral axial rotation and rotational instability have indeed been pointed out as a prominent characteristics of the scoliotic deformity in adolescents [30][31][32][33], and torsional buckling could occur more easily in a slender spine [15]. This work presents some limitations.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, mechanical instabilities due to rotational effects could be more relevant than lateral buckling, since intervertebral rotations at end vertebrae and higher torsion moments have been previously described [28,29]. Vertebral axial rotation and rotational instability have indeed been pointed out as a prominent characteristics of the scoliotic deformity in adolescents [30][31][32][33], and torsional buckling could occur more easily in a slender spine [15]. This work presents some limitations.…”
Section: Discussionmentioning
confidence: 88%
“…This overall displacement of the spinal midline can be accompanied by anterior overgrowth and lateral wedging of the vertebrae [11,12]. Recent works also showed that AIS patients can have increased spinal slenderness compared to asymptomatic controls [13][14][15]. Slenderness is "the ratio of transverse vertebral diameters to vertebral height […] combined into various slenderness ratios", according to the Scoliosis Research Society [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thoracic and lumbar vertebral height, from T1 to L5, as well as discal height, before and at latest follow-up were calculated as the mean of maximal anterior, posterior, left and right height in sagittal and coronal plane [25]. These measurements were compared to values obtained from the literature for healthy subjects [26].…”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…For the matched control, the identical levels as in the AIS patient were analyzed. The CT-scan analyses were performed using in-house developed software ( ScoliosisAnalysis 7.2, developed with MeVisLab, MeVis Medical Solutions AG, Bremen, Germany ), that was previously validated for curve morphology assessment [ 2 , 11 , 16 , 17 ]. One observer, semi-automatically segmented all the upper and lower vertebral body endplates and the spinal canal in the ‘true’ transverse plane by correcting for the coronal and sagittal angulation of each endplate (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…From existing pre-operative computed tomographic (CT) databases, patients with right-sided primary thoracic AIS (Lenke 1-4) and sex-and age matched healthy controls were included [10][11][12][13][14]. These patients received these CT-scans as part of their pre-operative work-up for planning of navigation guided pedicle screw placement, which in that university medical center is part of standard care for all idiopathic scoliosis patients with an indication for posterior instrumentation.…”
Section: Study Populationmentioning
confidence: 99%